Penerapan Metode PSI dan Moora pada Rekomendasi Pemilihan Laptop Terbaik untuk Desain Grafis berbasis Web - Yasmin, Anisa; Samsudin, Samsudin; Alda, Muhamad (Jurnal Manajemen Informatika, Sistem Informasi dan Teknologi Komputer (JUMISTIK), 2025)
This study develops a web-based decision support system to recommend the best laptops for graphic design purposes. The system combines the Preference Selection Index (PSI) method for criteria weighting and the Multi-Objective on the Basis of Ratio Analysis (MOORA) method for ranking alternatives. The research is motivated by the difficulty consumers face in selecting laptops with optimal specifications, such as powerful processors, discrete graphics, large RAM, and fast storage. The study was conducted at Raihan Computer Store, where recommendations were previously made based on intuition rather than data analysis. The proposed system offers data-driven recommendations by evaluating criteria such as performance, graphics, storage capacity, and price. This study is supported by previous research that demonstrates the effectiveness of PSI and MOORA methods. The results are expected to assist consumers in choosing suitable laptops for graphic design activities, thereby supporting learning or work in the field.